Kemoterapi Alan Kanserli Hastalarda Toksik Polinöropati Gelişimi - (:unkn) unknown (My University, 2016)
Amaç: Kanser ilaçlarının toksik etkilerine bağlı polinöropatilerin gelişme oranı ilaçlara göre değişkenlik göstermektedir. Bu çalışmada, taksan ve platin grubu kemoterapi alan hastalarda, ilaca bağlı toksik polinöropati gelişimi oranını belirleme amaçlandı.Gereç ve Yöntem: Bu çalışmaya taksan (doketaksel ve paklitaksel) ve platin (karboplatin ve sisplatin) alan hastalar alındı. Tüm hastalar klinik ve elektrofizyolojik olarak tedavi öncesi ve sonrası ilaca bağlı polinöropati açısından değerlendirildi. Polinöropati tespit edilen hastalarda anti-Yo, anti-Hu, anti-Ma2/Ta antikorlarına bakıldı.Bulgular: Toplam 123 hasta çalışmaya dâhil edildi. Yirmi iki tane (%17,8) hasta çalışmayı tamamlayamadan öldü. Tedavi almadan önce 12 hastada (%9,8) kansere bağlı polinöropati tespit edildi. Ölen ve tedavi öncesi kansere bağlı polinöropati gelişen toplam 34 hasta çalışmadan çıkarıldı. Kalan 89 hasta tedaviye alındı. Tedavi sonrası 50 hastada (%56,2) klinik ve elektrofizyolojik olarak kemoterapiye bağlı polinöropati tespit edildi. Paklitaksel+karboplatin alan 56 hastanın 33'ünde (%58,9) toksik polinöropati gelişti. Doketaksel+sisplatin alan 20 hastanın 10'unda (%50) toksik polinöropati gelişti. Her iki grup arasında polinöropati oluşturma açısından istatiksel olarak anlamlı fark gözlenmedi. Her iki grupta da polinöropati gelişimi kümülatif doz ile ilişkili olarak bulundu.Sonuç: İlaca bağlı gelişen toksik polinöropati paklitaksel ve doketaksel grubunda oldukça yüksek oranda gözlenmektedir. Bu sonuçlar bize doz yükseldikçe polinöropati gelişme oranı arttığını göstermektedir.

Objective: It was shown that rate of occurence of toxic polyneuropathy secondary to drugs used in cancer treatment, can show differences among cancer drugs. We aimed to evaluate chemotherapy induced toxic polyneuropathy in cancer patients who received taxane and platine. Material and Methods: We enrolled all patients who received taxane (docetaxel and paclitaxel) and platine (carboplatine and cisplatin). Each patient was evaluated clinically and electrophysiologically in terms of polyneuropathy before and after the treatment. In the patients with toxic polyneuropathy anti-Yo, anti-Hu, anti-Ma2/Ta antibodies were mesaured. Results: Totally 123 patients were included in the study. 22 of the patients (17.8%) died during the treatment. Twelve patients (9.8%), clinically and electrophysiologically was diagnosed with polyneuropathy before the treatment. Thirtyfour patients, who died or had polyneuropathy due to cancer before treatment were excluded from the study. Remaining 89 patients were included to the study. Following treatment, 50 of 89 patients (%56,2) had toxic polyneuropathy due to chemotherapy. 33 of 56 patients (58.9%) who were treated with paclitaxel +carboplatine had toxic polyneuropathy. 10 of 20 patients (50%) who received docetaxel+cisplatin had toxic polyneuropathy. There was no statistically significant difference between two groups in terms of inducing polyneuropathy. The risk of polyneuropathy in both groups were found to be related to the cumulative dose. Conclusion: Drug induced toxic polyneuropathy was found fairly high in patients who were treated with taxane and platine. The study pointed out that the toxic polyneuropathy rate is related to cumulative dose.
Chemotherapy Induced Toxic Polyneuropathy in Cancer Patients
Keywords: Hematoloji; Tıbbi Laboratuar Teknolojisi; Onkoloji